Multidisciplinary Approach to the Study of Ethnogenesis: Genogeography and Phylogeography of Tuvan Tribal Groups - Larissa D. Damba; Vladimir Yu. Pylev; Elena V. Balanovska (Oriental Studies, 2022)
Introduction. The territory of South Siberia has historically been a crossroads of ancient migration routes. So, the complex process of ethnogenesis across the region requires multidisciplinary insights of historians, ethnographers, anthropologists, linguists, and geneticists. Goals. The work aims to substantiate the possibility of a comprehensive study of Tuvan tribal groups on the basis of the latter’s gene pools and structures. Materials and methods. The most efficient tool thereto is the Y chromosome since it is inherited — like the clan/tribal name proper — paternally, has a high variety, makes it possible to reconstruct migration waves, and may yield genetic dates. These properties of the Y chromosome make it an additional historical source within comprehensive ethnographic, historical, linguistic, anthropological, and genetic studies of ancestral groups among peoples to have retained the memory of clan/tribal structures. Results. The early 21st century has witnessed an intensive research of the Tuvan Y-chromosomal gene pool — with no sufficient data on corresponding tribal groups mentioned. The analysis of Tuvan tribal structures is complicated by a number of factors, such as the administrative/territorial system of the Qing Empire in Tuva (1757–1912), introduction of a passport system in Tuva (1945–1947) when not clan/tribal names but rather personal ones were registered as surnames, and an increase in unmarried cohabitation that violates the patrilineal system. Y-chromosomal analyses of the largest Tuvan tribal groups Mongush and Oorzhak show that the bulk of their gene pool are North Eurasian haplogroups (N*, N1a2, N3a, Q) associated with the autochthonous population of the area nowadays inhabited by Tuvans. At the same time, Central Asian haplogroups (C2, O2) make up less than a fifth (17 %) of the gene pool. A targeted analysis of the most frequent branch (C2a1a2a2a2-SK1066) of the Central Asian haplogroup C2 shows it had originated about 900 years ago in the territory of Northeast Mongolia, and thus could not have reached Tuva before the 11th–12th centuries AD. Anthropological data also attest to the late admixture of the Central Asian cluster into the Tuvans and their tribal groups. The North Eurasian haplogroups completely dominate within the gene pool of tribal groups Kol, Oyun, and Khertek, which results in that the share of Central Asian lineages drops to 3%. Conclusions. In general, the paper shows the Mongolian expansion had no essential genetic impacts on the Y-chromosomal gene pool of Tuvan tribal groups, but — in contrast — did overwhelmingly influence ethnocultural, economic, and linguistic spheres.